Doubly robust estimation of causal effects with multivalued treatments - S. Derya Uysal (Institute for Advanced Studies (IHS), 2013)
This paper provides doubly robust estimators for treatment effect parameters which are defined in multivalued treatment effect framework. We apply this method on a unique data set of British Cohort Study (BCS) to estimate returns to different levels of schooling. Average returns are estimated for entire population, as well as conditional on having a specific educational achievement. The analysis is carried out for female and male samples separately to capture possible gender differences. The results indicate that, on average, the percentage wage gain due to higher education versus any other lower educational attainment is higher for highly educated females than highly educated males.
Keywords: C21; J24; I2; 330; Multivalued treatment; returns to schooling; doubly robust estimation; Bildungsertrag; Robustes Verfahren; Schätzung; Großbritannien